THE PROFILE OF STUDENTS’ EMPLOYMENT IDENTITY STATUS (A STUDY AT PUBLIC HEALTH EDUCATION STUDY PROGRAM, FKIP UNIVERSITAS RIAU) - Wilson; Daeng Ayub; Said Suhil; Titi Maemunaty (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Teenagers studying at university, known as college students, have the responsibility for themselves; they are demanded to be independent in academic activities as well as to build the identity achievement by searching for information through exploration with sufficient intensity in various fields. After collecting adequate information, they need to make choices (commitment) to the field that suits thei interests and abilities. Based on a discussion conducted in the class, it was revealed that some students felt unsuitable with the study program they took; they did not know the career they would pursue while they were already in the third and fourth semesters. This was survey research with a quantitative approach. This study aimed to obtain an objective description of the Students’ Employment Identity Status at the Public Health Education FKIP Universitas Riau. The samples of this study were taken randomly from a population of 104 students. Data on the students’ (adolescents) identity status were collected through a questionnaire. Then, the data were analyzed by using descriptive statistical analysis utilizing SPSS 20. The results of the study found that only 30.77% of students reached the achievement status while 42.31% of the students were at the level of moratorium status. In addition, 15.38% of the students at the level of Forclusure identity status and 11.54% of them were at the level of diffusion status.